Biological plausibility as a tool to associate analytical data for micropollutants and effect potentials in wastewater, surface water, and sediments with effects in fishes. (1st April 2015) - Maier, Diana; Blaha, Ludek; Giesy, John P.; Henneberg, Anja; Köhler, Heinz-R.; Kuch, Bertram; Osterauer, Raphaela; Peschke, Katharina; Richter, Doreen; Scheurer, Marco; Triebskorn, Rita
Abstract: Discharge of substances like pesticides, pharmaceuticals, flame retardants, and chelating agents in surface waters has increased over the last decades due to the rising numbers of chemicals used by humans and because many WWTPs do not eliminate these substances entirely. The study, results of which are presented here, focused on associations of (1) concentrations of micropollutants in wastewater treatment plant (WWTP) effluents, surface waters, sediments, and tissues of fishes; (2) results of laboratory biotests indicating potentials for effects in these samples and (3) effects either in feral chub ( Leuciscus cephalus ) from two German rivers (Schussen, Argen) or in brown trout ( Salmo trutta f. fario ) and rainbow trout ( Oncorhynchus mykiss ) exposed in bypass systems to streamwater of these rivers or in cages directly in the rivers. The Schussen and Argen Rivers flow into Lake Constance. The Schussen River is polluted by a great number of chemicals, while the Argen River is less influenced by micropollutants. Pesticides, chelating agents, flame retardants, pharmaceuticals, heavy metals, polychlorinated biphenyls (PCBs), and polybrominated diphenyl ethers (PBDEs) were detected in effluents of a WWTP discharging to the Schussen as well as in surface water, and/or fishes from downstream of the WWTP. Results obtained by biotests conducted in the laboratory (genotoxicity, dioxin-like toxicity, and embryotoxicity) were linked to effects in feral fish collected in the vicinity of the WWTP or in fishes exposed in cages or at the bypass systems downstream of the WWTP. Dioxin-like effect potentials detected by reporter gene assays were associated with activation of CYP1A1 enzymes in fishes which are inducible by dioxin-like chemicals. Abundances of several PCBs in tissues of fishes from cages and bypass systems were not associated with these effects but other factors can influence EROD activity. Genotoxic potentials obtained by in vitro tests were associated with the presence of micronuclei in erythrocytes of chub from the river. Chemicals potentially responsible for effects on DNA were identified. Embryotoxic effects on zebrafish ( Danio rerio ), investigated in the laboratory, were associated with embryotoxic effects in trout exposed in streamwater bypass systems at the two rivers. In general, responses at all levels of organization were more pronounced in samples from the Schussen than in those from the Argen. These results are consistent with the magnitudes of chemical pollution in these two streams. Plausibility chains to establish causality between exposures and effects and to predict effects in biota in the river from studies in the laboratory are discussed. Graphical abstract: Highlights: This study included chemical analysis, laboratory biotests, and field studies. Focus on non-endocrine effects. Pollution was higher downstream of the wastewater treatment plant. Stronger effects downstream of the wastewater treatment plant. Linkage established between chemical analysis, lab biotests, and field effects.